Enhancing Legal Safeguards for Human Trafficking Victims in Indonesia - Sari, Pika; Yanuarto, Totok; Prihatmini, Sapti; Amirullah, Arif; Tanuwijaya, Fanny (Jurnal Hukum Magnum Opus, 2024)
Human trafficking constitutes one of the most egregious forms of human rights violations, characterized by extensive criminal networks operating at both individual and group levels. This phenomenon is not new, and certain countries, including Indonesia, report high incidences of human trafficking-related crimes. The purpose of this research is to provide an evaluation and understanding of the legal protections available to victims of human trafficking in Indonesia. This study is classified as normative legal research, involving an examination of theories, concepts, legal principles, and relevant statutory provisions pertaining to the topic. Despite significant efforts by the Indonesian government to combat human trafficking, minimum standards for eradication have not been fully met. While there have been notable advancements compared to previous periods, especially in response to the challenges posed by the COVID-19 pandemic, substantial deficiencies remain. Indonesia's upgrade to Tier 2 reflects progress in the investigation, prosecution, and adjudication of human trafficking offenses, including cases of forced labor in palm oil plantations and cyber fraud operations abroad. Additionally, there have been efforts to enhance compensation for victims of human trafficking.